Short-term outcomes in the upper airway with tooth-bone-borne vs bone-borne rapid maxillary expanders - Javier Echarri-Nicolás; María José González-Olmo; Pablo Echarri-Labiondo; Martin Romero (BMC Oral Health, 2023)
Abstract Background This study compared the area and minimal section of the nasal cavity, nasopharynx, oropharynx, and hypopharynx in cases treated with different methods of microimplant-assisted expansion. Methods Based on a pilot study to calculate the sample size, 30 patients with transverse maxillary deficiency over 14 years of age were retrospectively selected. These patients had received two different types of microimplant-assisted maxillary expansion treatment (MARPE and BAME). The patient underwent Cone-Beam computed tomography (CBCT) before and after treatment (mean time 1.5 months) with MARPE or BAME and upper airway measurements (volume and minimum cross-sectional area) were taken to assess upper airways changes and compare changes between the groups. A paired sample t-test was performed to evaluate the T0-T1 change of airway measurements obtained with MARPE and BAME, and a student t-test to compare changes in airway measurements between MARPE and BAME. Results This investigation shows a statistically significant increase in total nasopharyngeal airway volume (0.59 ± 1.42 cm3; p < 0.01), total oropharyngeal airway volume (3.83 ± 7.53 cm3; p < 0.01) and minimum oropharyngeal cross-section (53.23 ± 126.46 mm2; p < 0.05) in all cases treated with micro-screw assisted expansion. The minimal cross-sectional area of the oropharynx ((79.12 ± 142.28 mm2; p < 0.05) and hypopharynx (59.87 ± 89.79 mm2; p < 0.05) showed significant changes for cases treated with BAME. As for the comparison between cases treated with MARPE and BAME, no differences in upper airway changes have been observed, except for the minimum cross-sectional area of the nasal cavity, which increases for MARPE (52.05 ± 132.91 mm2) and decreases for BAME (-34.10 ± 90.85 mm2). Conclusions A significant increase in total area and minimal section at the level of nasopharynx and oropharynx was observed in cases treated with BAME. Regarding the comparison of MARPE and BAME treatments, no differences were found in the total airway volume and minimal section in upper airway except for the minimum cross section of the nasal cavity that increases for MARPE and decreases for BAME.